Development of Photoactivated Fluorescent N‐Hydroxyoxindoles and Their Application for Cell‐Selective Imaging. Issue 18 (23rd March 2016) - Lai, Jinping; Yu, An; Yang, Letao; Zhang, Yixiao; Shah, Birju P.; Lee, Ki Bum
Abstract: Photoactivatable fluorophores are essential tools for studying the dynamic molecular interactions within important biological systems with high spatiotemporal resolution. However, currently developed photoactivatable fluorophores based on conventional dyes have several limitations including reduced photoactivation efficiency, cytotoxicity, large molecular size, and complicated organic synthesis. To overcome these challenges, we herein report a class of photoactivatable fluorescent N ‐hydroxyoxindoles formed through the intramolecular photocyclization of substituted o ‐nitrophenyl ethanol (ONPE). These oxindole fluorophores afford excellent photoactivation efficiency with ultra‐high fluorescence enhancement (up to 800‐fold) and are small in size. Furthermore, the oxindole derivatives show exceptional biocompatibility by generating water as the only photolytic side product. Moreover, structure–activity relationship analysis clearly revealed the strong correlation between the fluorescent properties and the substituent groups, which can serve as a guideline for the further development of ONPE‐based fluorescent probes with desired photophysical and biological properties. As a proof‐of‐concept, we demonstrated the capability of a new substituted ONPE that has an uncaging wavelength of 365–405 nm and an excitation/emission at 515 and 620 nm, for the selective imaging of a cancer cell line (Hela cells) and a human neural stem cell line (hNSCs). Abstract : Seeing stem cells : Photocyclization of substituted o ‐nitrophenyl ethanol (ONPE) leads to the formation of fluorescent N ‐hydroxyoxindole with high efficiency and up to 800‐fold fluorescence (Fl) enhancement (see figure). The optical properties of the oxindole can be flexible and an ONPE derivative with a Vis excitation (>500 nm) and a NIR emission (620 nm) has been developed for the spatially‐controlled cell‐selective imaging of human neural stem cells (hNSCs).